A laser cladding repair method of a non-magnetic drill rod and a surface-repaired non-magnetic drill rod

CN122918563APending Publication Date: 2026-10-16SHAANXI TAIHE TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611246274.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种无磁钻杆的激光熔覆修复方法及表面修复型无磁钻杆,为解决现有技术中修复层耐腐蚀性能难以超越基材的技术问题

Benefits of technology

(1)本发明采用Stellite 6钴基合金粉末对1Cr18Mn18N无磁钻杆进行激光熔覆修复,所得修复层在3% NaCl溶液中的腐蚀电流密度显著低于基体,自腐蚀电位显著高于基体,实现了修复层耐腐蚀性能对基材的实质性超越。不同于现有不锈钢粉末或镍基粉末修复技术仅能追求“达到基材性能”的技术瓶颈,本发明首次在无磁钻杆激光熔覆修复领域实现了修复层耐腐蚀性能全面优于基材的技术突破,尤其适用于深层、超深层及可燃冰等富含Cl-腐蚀介质的严苛油气藏钻采作业环境,可有效延长无磁钻杆在腐蚀工况下的服役寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918563A_ABST
    Figure CN122918563A_ABST
Patent Text Reader

Abstract

This invention discloses a laser cladding repair method for non-magnetic drill rods and a surface-repairable non-magnetic drill rod, belonging to the field of non-magnetic drill rod repair technology. The method includes: machining, cleaning, sandblasting, and preheating the area to be repaired on the non-magnetic drill rod; drying Stellite 6 cobalt-based alloy powder, and then performing laser cladding using process parameters of 1.8–2.2 kW laser power, 2.5–3.5 mm spot diameter, 8–15 mm / min scanning speed, 200–300 mm³ / min powder feed rate, and 1.2–1.8 mm scanning spacing. The cladding path spirals along the drill rod axis, with a single pass thickness of 1.2–1.8 mm, and 2–3 layers are clad together, for a total thickness of 3–5 mm; followed by natural cooling and polishing. The repair layer prepared by this method exhibits a lower corrosion current density and relative magnetic permeability in 3% NaCl solution than the substrate. μ r With a strength of <1.01 and a hardness of 39-42 HRC, it achieves a substantial improvement in corrosion resistance over the base material, while also being non-magnetic and wear-resistant, effectively extending the life of non-magnetic drill rods and reducing drilling costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of non-magnetic drill rod repair technology, and more specifically, to a laser cladding repair method for non-magnetic drill rods and a surface-repairable non-magnetic drill rod. Background Technology

[0002] Non-magnetic drill pipes are special drill pipes that remain non-magnetic in the Earth's magnetic field. They are typically made of high-strength non-magnetic alloy materials (such as high-nitrogen, chromium-manganese, non-magnetic stainless steel) and are widely used in geological exploration and oil drilling. Their core advantage lies in avoiding interference with the measurement accuracy of precision downhole instruments such as magnetometers. However, non-magnetic drill pipes experience severe wear on their outer diameter during service, often exceeding dimensional tolerances and requiring premature scrapping. To reduce procurement costs, the industry has begun exploring repair and reuse technologies for scrapped non-magnetic drill pipes. In recent years, as oil and gas development has gradually extended to deep, ultra-deep, and methane hydrate reservoirs, downhole corrosion and wear conditions have become increasingly severe, placing higher demands on the service life and reliability of drilling equipment. Therefore, the repair and reuse of non-magnetic drill pipes has demonstrated significant engineering value and economic benefits.

[0003] Laser cladding technology, as a green and energy-saving advanced additive manufacturing technology, has been commercially applied in the field of oil drilling equipment repair. Besides laser cladding, existing technologies also include consumable electrode arc welding (MEA) for repairing non-magnetic drill pipe joints. For example, some researchers have chosen MEA to repair worn joints of non-magnetic pressure drill pipes and designed metal powder-core wire suitable for repairing wear and uneven wear of non-magnetic drill pipe joints. However, this traditional arc welding repair method has inherent defects such as a large heat-affected zone and low coating bonding strength. Furthermore, the magnetism of the cladding layer after welding is difficult to control, making it difficult to meet the requirements of non-magnetic drill pipes for relative magnetic permeability. m r The requirement of <1.01 is stringent; on-site measurements show that the width of the heat-affected zone can reach 2~4mm, and the workpiece is prone to peeling and delamination failure after about 300 hours of service. The magnetic permeability of the weld overlay generally exceeds the 1.01 threshold.

[0004] In addition, some existing laser cladding repair solutions have attempted a dual-layer structure design. First, a nickel-based non-magnetic or weakly magnetic undercoating layer is laser-clad onto the surface of the non-magnetic drill collar to be strengthened. Then, a high-hardness nickel-based wear-resistant cladding layer is laser-clad on top of the undercoating layer to address the risks of cracking and porosity in the high-hardness wear-resistant material. This dual-layer structure primarily focuses on surface wear resistance strengthening and does not specifically optimize corrosion resistance. The corrosion resistance of the repair layer only reaches a level comparable to the base material, making it difficult to meet the higher requirements for corrosion resistance of drilling equipment in harsh oil and gas reservoir environments such as deep and ultra-deep formations. After repair, the drill pipe remains susceptible to corrosion damage in high Cl₂ environments. - The service life of H2S-corroded well sections is only 3 to 6 months.

[0005] Currently, laser cladding repair of non-magnetic drill pipes mostly uses stainless steel powder or nickel-based powder as cladding materials. However, limited by the inherent corrosion resistance of these materials, the corrosion resistance of the resulting repair layer typically only reaches a level comparable to the substrate, failing to substantially surpass the substrate's corrosion resistance. Field corrosion test data shows that conventional nickel-based and stainless steel cladding layers exhibit less than a 5% reduction in corrosion current density compared to the 1Cr18Mn18N substrate in 3% NaCl medium, with some stainless steel cladding layers even showing higher corrosion currents. As the demands on drill pipe service life increase in highly corrosive downhole environments, there is an urgent need to develop new cladding materials and supporting processes. These materials should significantly enhance the repair layer's resistance to pitting corrosion, stress corrosion, and other localized corrosion while maintaining non-magnetic properties, enabling the repair layer's corrosion resistance to comprehensively surpass that of the substrate. This would better meet the higher requirements for drill pipe service life under complex operating conditions. Summary of the Invention

[0006] The purpose of this invention is to provide a laser cladding repair method for non-magnetic drill rods and a surface-repair type non-magnetic drill rod, in order to solve the technical problem that the corrosion resistance of the repair layer is difficult to exceed that of the substrate in the prior art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A laser cladding repair method for non-magnetic drill rods, wherein the base material of the non-magnetic drill rod is 1Cr18Mn18N non-magnetic stainless steel, includes the following steps: Step 1: Pre-treatment of the repair area: The area to be repaired on the non-magnetic drill rod substrate is machined to remove the surface damage layer, cleaned, and then sandblasted to achieve a surface roughness Ra of 10–25 μm. Preheating is then performed at 350–450 ℃. The thickness of the damage layer removed by machining is controlled to 0.3–0.8 mm to thoroughly remove fatigue cracks and corrosion pits from the substrate surface. After sandblasting, the temperature is uniformly increased to 350–450 ℃ at a rate of 50–80 ℃ / h to avoid sudden heating and internal residual stress. Random surface roughness is checked after sandblasting; only after all roughnesses meet the Ra 10–25 μm requirement can the preheating process begin. Step 2, Preparation of Repair Welding Material: Dry the Stellite 6 cobalt-based alloy powder; select Stellite 6 cobalt-based powder with a particle size of 45~106μm. If the powder is too fine, it is easy to burn off at high temperature in the laser molten pool and produce pores. If the powder is too coarse, it will cause incomplete melting and reduced interfacial bonding strength. After the powder is dried, it is stored in a vacuum-sealed container to avoid moisture absorption and re-introduction of moisture. The high Cr element in the powder can form a dense passivation film in the chloride ion medium, the W element improves the resistance to erosion and wear, and the Co matrix ensures the weak magnetic stability of the cladding layer. Step 3: Laser Cladding Repair Layer: Dry-treated Stellite 6 cobalt-based alloy powder is used to laser clad the area to be repaired, forming a repair layer. The laser cladding process parameters are: laser power 1.8–2.2 kW, spot diameter 2.5–3.5 mm, scanning speed 8–15 mm / min, powder feed rate 200–300 mm³ / min, scanning interval 1.2–1.8 mm, protective gas is argon, gas flow rate 12–18 L / min; the cladding path adopts a spiral trajectory along the axis of the non-magnetic drill rod, covering the outer circumferential surface of the area to be repaired. The thickness of a single cladding layer is 1.2–1.8 mm, with a total of 2–3 layers clad, for a total thickness of 3–5 mm; the axial feed per turn of the cladding spiral trajectory and the scanning interval are 1.2–1.8 mm. Matching ensures uniform thickness of the circumferential repair layer on the drill pipe; during multi-layer cladding, the workpiece temperature is maintained at ≥300℃ before the next layer is clad to prevent cold interlayers and poor interface bonding defects; a double-layer gas protection system of inner coaxial argon and outer auxiliary argon is used to further isolate the molten pool from air and prevent oxidation; the overall dilution rate of this process is controlled within 3% to avoid dilution of the high manganese and nitrogen elements in the matrix, which would damage the non-magnetic and corrosion-resistant core properties of the cladding layer. The dilution rate of conventional nickel-based cladding processes can reach 8%~15%. Step 4: Post-cladding treatment: After cladding, cool to room temperature and grind the surface of the cladding layer to make the surface roughness Ra ≤ 1.6 μm. Grinding is divided into two processes: rough grinding to remove surface spatter and protrusion defects, and then fine grinding to Ra≤1.6μm. After grinding, a penetrant testing (PT) non-destructive testing process is added to comprehensively check for microcracks and subcutaneous pores inside the cladding layer. Only after passing the test can it be stored naturally.

[0008] Preferably, the sandblasting treatment in step one uses brown corundum sand with a particle size of 30-40 mesh.

[0009] Preferably, in step one, anhydrous ethanol is used to clean the oil stains on the surface to be repaired.

[0010] Preferably, the drying temperature in step two is 100–150 °C, and the drying time is 1.5–3 h.

[0011] Preferably, the laser cladding process parameters in step three are: laser power 1.9 kW, spot diameter 3 mm, scanning speed 10 mm / min, powder feeding rate 250 mm³ / min, scanning spacing 1.5 mm, and argon gas flow rate 15 L / min.

[0012] Preferably, the cooling in step four is natural cooling.

[0013] Preferably, in step one, after sandblasting, the surface dust is blown away and then preheating is performed.

[0014] Preferably, the corrosion current density of the repair layer in a 3% NaCl solution at room temperature is lower than that of the 1Cr18Mn18N non-magnetic stainless steel substrate, and the relative magnetic permeability of the repair layer is... m r Less than 1.01.

[0015] Preferably, the Rockwell hardness of the repair layer is 39-42 HRC, and the Rockwell hardness of the 1Cr18Mn18N non-magnetic stainless steel substrate is 35-40 HRC.

[0016] A surface-repairable non-magnetic drill rod, prepared by the above method, includes a non-magnetic drill rod substrate. A laser cladding repair layer is disposed on the surface of the area to be repaired of the non-magnetic drill rod substrate. The laser cladding repair layer is formed by laser cladding of Stellite 6 cobalt-based alloy powder. The thickness of the laser cladding repair layer is 3–5 mm, consisting of 2–3 cladding layers stacked together. The surface roughness Ra ≤ 1.6 μm, and the Rockwell hardness is 39–42 HRC. The corrosion resistance of the laser cladding repair layer is superior to that of the non-magnetic drill rod substrate, and the relative magnetic permeability of the laser cladding repair layer is also superior. m r Less than 1.01.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses Stellite 6 cobalt-based alloy powder to laser clad repair 1Cr18Mn18N non-magnetic drill rods. The resulting repair layer exhibits a significantly lower corrosion current density and a significantly higher self-corrosion potential in 3% NaCl solution than the substrate, achieving a substantial improvement in corrosion resistance over the substrate. Unlike existing stainless steel powder or nickel-based powder repair technologies that only aim to "achieve substrate performance," this invention represents a groundbreaking breakthrough in the field of laser cladding repair of non-magnetic drill rods, achieving comprehensive superior corrosion resistance of the repair layer compared to the substrate. It is particularly suitable for deep, ultra-deep, and Cl-rich environments such as methane hydrate. - The harsh drilling and production environment of oil and gas reservoirs with corrosive media can effectively extend the service life of non-magnetic drill pipes under corrosive conditions.

[0018] (2) While improving corrosion resistance, the Rockwell hardness (39-42 HRC) of the cladding layer is not lower than that of the substrate (35-40 HRC), and it has better wear resistance than the substrate; the relative magnetic permeability of the cladding layer m r ≈ 1.001, matrix m rThe values ​​are approximately 1.003, all less than 1.01, meeting the stringent requirements for non-magnetic properties in non-magnetic drill rods. This invention achieves synergistic optimization of three major performance aspects: improved corrosion resistance, enhanced hardness / wear resistance, and maintained non-magnetic properties, avoiding the technical defect of sacrificing other key performance aspects for improving a single performance. In existing stainless steel powder laser cladding repair solutions, the problem of uneven bonding interfaces in multi-layer cladding is quite prominent. The Stellite 6 cobalt-based alloy powder used in this invention has good fluidity and wettability, making powder splashing and loss relatively controllable during laser cladding. Repair consistency and surface roundness are easier to ensure, effectively avoiding the process defects of uneven bonding interfaces in multi-layer cladding in stainless steel powder repair, and ensuring the overall quality and service reliability of the repair layer.

[0019] (3) This invention utilizes laser cladding technology to simultaneously melt and rapidly solidify a thin layer of Stellite 6 cobalt-based alloy powder onto the substrate surface. This creates a dense, pore-free, and crack-free metallurgical interface between the repair layer and the substrate, resulting in a bonding strength far exceeding that of traditional arc welding and other repair methods. The repair layer is less prone to peeling or delamination during use, significantly improving the reliability and service life of the repaired non-magnetic drill rod. The laser cladding repair method provided by this invention can be applied to both outer diameter wear and localized damage repair of non-magnetic drill rods. By adjusting the laser cladding process parameters, it can be applied to non-magnetic drill rods of different damage levels and specifications, offering a wide range of applications and good process compatibility and engineering practicality. This invention, by replacing complete replacement with laser cladding repair, can significantly reduce the procurement cost of non-magnetic drill rods and significantly extend the service life of drilling tools, resulting in significant economic benefits. Furthermore, the process flow of this invention is complete and controllable. The Stellite 6 cobalt-based alloy powder exhibits good process stability, enabling stable batch industrial repair of scrapped non-magnetic drill rods, and possessing promising prospects for industrial promotion.

[0020] (4) The repairable non-magnetic drill pipe prepared by the present invention maintains the non-magnetic properties while its corrosion resistance surpasses that of the base material, and its hardness and wear resistance are not lower than those of the base material. The overall performance of the repaired drill pipe meets the requirements for non-magnetic use in magnetic exploration wells. It can effectively cope with the higher requirements for the service life of drilling and production equipment in the high corrosion and high wear downhole working conditions of complex oil and gas reservoirs such as deep, ultra-deep and combustible ice. It can replace the use of brand new non-magnetic drill pipes and provide technical support for safe and efficient drilling and production in harsh oil and gas reservoirs. Attached Figure Description

[0021] Figure 1 This is a flowchart of the laser cladding repair process for non-magnetic drill rods according to the present invention; Figure 2 This is a schematic diagram of the cross-section of the drill pipe after cladding repair according to the present invention.

[0022] The labels in the diagram are as follows: 1. Non-magnetic drill rod substrate; 2. Laser cladding repair layer. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0024] Example 1: Please see Figure 1 A laser cladding repair method for non-magnetic drill rods is disclosed, used for surface repair of damaged non-magnetic drill rods made of 1Cr18Mn18N non-magnetic stainless steel. The specifications of the non-magnetic drill rod to be repaired are as follows: outer diameter 89 mm, wall thickness 13 mm, and length 1.5 m.

[0025] I. Pre-treatment of the repair area First, a comprehensive inspection of the non-magnetic drill rod is conducted to determine the type of damage in the area to be repaired (including outer diameter wear and local defects). Then, machining methods (such as turning) are used to remove the surface damage layer of the base material in the area to be repaired until the complete metal substrate is exposed.

[0026] Clean the surface to be repaired with anhydrous ethanol to remove oil and other contaminants. After cleaning, sandblast the surface with 30-40 mesh brown corundum abrasive to achieve a surface roughness Ra of 10-25 μm. The purpose of sandblasting is to remove the surface oxide layer and increase surface roughness, thereby improving the bonding strength between the cladding material and the substrate during subsequent laser cladding. After sandblasting, blow away any surface dust with compressed air.

[0027] The sandblasted non-magnetic drill rod is placed in a preheating device for preheating treatment at a temperature of 350–450°C. In this embodiment, the preferred preheating temperature is 400°C. The purpose of the preheating treatment is to reduce the temperature gradient between the cladding layer and the substrate during laser cladding, reduce the cracking tendency of the cladding layer, and improve the bonding quality between the cladding layer and the substrate.

[0028] II. Preparation of Welding Materials for Repair Stellite 6 cobalt-based alloy powder was selected as the cladding material, with a particle size of 45–106 μm. The typical mass fraction composition of commercial standard Stellite 6 alloy is: Cr 28%–32%, W 4%–6%, C 0.9%–1.3%, Si≤2%, Mn≤2%, with the balance being Co. Stellite 6 cobalt-based alloy is a cobalt-based alloy with a high content of chromium and tungsten. The high chromium content forms a dense passivation film in chloride-corrosive media, while the tungsten content enhances high-temperature wear resistance and erosion resistance, resulting in excellent overall corrosion resistance, wear resistance, and high-temperature performance. Before laser cladding, the Stellite 6 cobalt-based alloy powder was dried in a drying oven at 100–150 °C for 1.5–3 h. In this embodiment, the preferred drying conditions were constant temperature drying at 120 °C for at least 2 h to remove excess moisture adsorbed in the powder and prevent porosity defects caused by moisture vaporization during laser cladding.

[0029] III. Laser Cladding Repair Layer Using dried Stellite 6 cobalt-based alloy powder, a fiber laser and a coaxial powder feeding cladding machine are employed to perform laser cladding on the area to be repaired on a non-magnetic drill rod, forming a repair layer. The specific process parameters for laser cladding are as follows: laser power 1.8–2.2 kW, spot diameter 2.5–3.5 mm, scanning speed 8–15 mm / min, powder feeding rate 200–300 mm³ / min, scanning interval 1.2–1.8 mm, and argon gas as the protective gas with a flow rate of 12–18 L / min. In this embodiment, the preferred laser cladding process parameters are: laser power 1.9 kW, spot diameter 3 mm, scanning speed 10 mm / min, powder feeding rate 250 mm³ / min, scanning interval 1.5 mm, and argon gas flow rate 15 L / min. The determination of the above process parameter range takes into account multiple factors such as the forming quality, density, bonding strength and production efficiency of the cladding layer: too low laser power will lead to insufficient powder melting and poor bonding, while too high power may cause excessive dilution of the substrate and expansion of the heat-affected zone; the scanning speed and powder feeding rate need to be matched to ensure sufficient powder supply and appropriate heat input per unit area; the setting of the scanning spacing directly affects the overlap quality between adjacent cladding channels. Too large a spacing will easily produce unoverlapped areas, while too small a spacing will cause unnecessary repeated cladding.

[0030] The cladding path adopts a spiral trajectory along the axis of the non-magnetic drill rod, covering the outer circumferential surface of the area to be repaired. The spiral cladding path ensures the uniformity of the repair layer thickness across the entire outer circumferential surface, avoiding uneven thickness caused by overlapping or insufficient overlap. The thickness of a single cladding layer is 1.2–1.8 mm; in this embodiment, the preferred thickness is 1.5 mm. A total of 2–3 layers are clad, resulting in a total repair layer thickness of 3–5 mm. This multi-layer cladding method facilitates the gradual release of thermal stress during the cladding process, reducing the risk of cracking in the repair layer. Simultaneously, the multi-layer stacking ensures that the repair layer achieves the required thickness, meeting the restoration requirements of the non-magnetic drill rod's outer diameter.

[0031] During laser cladding, high-energy laser beam irradiation causes Stellite 6 cobalt-based alloy powder and a thin layer on the substrate surface to melt simultaneously, followed by rapid solidification, forming a surface repair layer with extremely low dilution and metallurgical bonding with the substrate. A dense metallurgical interface without pores or cracks is formed between the cladding layer and the substrate, resulting in high bonding strength and resistance to peeling.

[0032] IV. Post-cladding treatment After laser cladding is completed, the non-magnetic drill rod is allowed to cool naturally to room temperature. Natural cooling avoids excessive thermal stress caused by rapid cooling, which helps ensure the uniformity of the repair layer's structure and dimensional stability.

[0033] After cooling to room temperature, the surface of the cladding layer is polished to remove spatter and uneven areas generated during the cladding process. Polishing can be done by grinding with a grinding wheel or turning to ensure that the surface roughness Ra of the cladding layer is ≤ 1.6 μm, in order to meet the surface quality requirements of the non-magnetic drill rod.

[0034] like Figure 2 As shown, a surface-repairable non-magnetic drill rod is prepared by the laser cladding repair method described above. It includes a non-magnetic drill rod substrate 1, with a laser cladding repair layer 2 formed from Stellite 6 cobalt-based alloy powder via laser cladding. The thickness of the laser cladding repair layer 2 is 3–5 mm, consisting of 2–3 cladding layers, with a surface roughness Ra ≤ 1.6 μm and a Rockwell hardness of 39–42 HRC. The corrosion resistance of the laser cladding repair layer 2 is superior to that of the non-magnetic drill rod substrate, and the relative magnetic permeability of the laser cladding repair layer is also superior. m r Less than 1.01.

[0035] V. Performance Testing (1) The performance of the non-magnetic drill rod repaired by the above method was tested, as follows: Under room temperature conditions, using 3% NaCl solution as the corrosion medium and a conventional three-electrode electrochemical workstation, the electrochemical corrosion behavior of the cladding layer and the 1Cr18Mn18N non-magnetic drill rod substrate was tested by linear polarization method. The test results show that the cladding layer has a lower corrosion current density and a higher self-corrosion potential, indicating that the corrosion resistance of the cladding layer is significantly better than that of the base material. Stellite 6 cobalt-based alloy contains a high content of Cr (approximately 28%–30%) and W alloying elements, which can form a stable passivation film in the corrosive medium, thereby effectively improving its resistance to Cl. - The ability to prevent pitting and stress corrosion.

[0036] (2) Hardness test The hardness of the cladding layer and the substrate was tested using a benchtop digital Rockwell hardness tester, with the HRC standard test load uniformly selected. The test results show that the Rockwell hardness of the 1Cr18Mn18N non-magnetic stainless steel substrate is approximately 35–40 HRC, and the Rockwell hardness of the cladding layer is approximately 39–42 HRC. The hardness of the cladding layer is not lower than that of the substrate, which meets the working requirements of non-magnetic drill rods.

[0037] (3) Magnetic test At room temperature, the relative permeability of the cladding layer and the substrate was measured using a portable relative permeability meter. m r Test results show that the relative magnetic permeability of the 1Cr18Mn18N non-magnetic stainless steel matrix is... m r ≈ 1.003, relative permeability of the cladding layer m r ≈ 1.001, both are less than 1.01, both meet the strict requirements of non-magnetic drill rods for non-magnetic properties, and will not interfere with the measurement accuracy of downhole precision instruments such as magnetometers.

[0038] Example 2 The difference between this embodiment and Embodiment 1 is as follows: the preheating temperature in step one is 350 ℃; the drying temperature in step two is 100 ℃, and the drying time is 3 h; the laser cladding process parameters in step three are: laser power 1.8 kW, spot diameter 2.5 mm, scanning speed 8 mm / min, powder feeding rate 200 mm³ / min, scanning spacing 1.2 mm, argon gas flow rate 12 L / min; the thickness of a single cladding layer is 1.2 mm, with a total of 3 cladding layers, and the total thickness of the repair layer is approximately 3.6 mm. Testing showed that the repair layer prepared in this embodiment also exhibits superior corrosion resistance compared to the substrate, a hardness not lower than the substrate, and a relative permeability less than 1.01.

[0039] Example 3 The difference between this embodiment and Embodiment 1 is as follows: the preheating temperature in step one is 450 ℃; the drying temperature in step two is 150 ℃, and the drying time is 1.5 h; the laser cladding process parameters in step three are: laser power 2.2 kW, spot diameter 3.5 mm, scanning speed 15 mm / min, powder feeding rate 300 mm³ / min, scanning spacing 1.8 mm, and argon gas flow rate 18 L / min; the thickness of a single cladding layer is 1.8 mm, with two layers clad together, resulting in a total repair layer thickness of approximately 3.6 mm. Testing showed that the repair layer prepared in this embodiment also exhibits superior corrosion resistance compared to the substrate, a hardness not lower than the substrate, and a relative permeability less than 1.01.

[0040] Comprehensive performance test results of cladding layer 1. Electrochemical corrosion test A 720-hour long-term immersion test in 3% NaCl was added for comparison: a large number of pitted corrosion pits appeared on the surface of the 1Cr18Mn18N substrate, while the surface of the Stellite 6 repair layer showed no corrosion defects; electrochemical data from the three sets of examples showed that the corrosion current density of the repair layer was reduced by more than 40% compared with the substrate, and the self-corrosion potential was positively increased by ≥120mV.

[0041] 2. Hardness and wear resistance A comparative test of dry friction and wear at room temperature was conducted. Under the same load conditions, the wear of the cladding layer of this invention was reduced by more than 35% compared with the 1Cr18Mn18N substrate, and its wear resistance was significantly better than that of the substrate.

[0042] 3. Combined strength test Tensile tests showed that the metallurgical bond strength between the cladding layer and the substrate was ≥620MPa, while the bond strength of the traditional arc welding repair layer was only 380~450MPa, which significantly reduced the risk of spalling and delamination failure in the well.

[0043] 4. High-temperature non-magnetic properties Simulated 150℃ deep downhole high-temperature test, relative magnetic permeability of the repair layer m r It remains stable at less than 1.01, and its non-magnetic properties do not decay under high temperature environments, making it suitable for ultra-deep, high-temperature oil and gas well operations.

[0044] Industrial applicability The laser cladding repair method for non-magnetic drill rods provided by this invention can be applied to both outer diameter wear and localized damage repair, making it widely applicable. By replacing the entire drill rod with a repair method, the procurement cost of non-magnetic drill rods can be significantly reduced, and the service life of the drill bit can be extended. It is especially suitable for the repair and reuse of non-magnetic drill rods in harsh oil and gas reservoir environments such as deep, ultra-deep, and combustible ice reservoirs. Stellite 6 cobalt-based alloy powder has good flowability and wettability, and the powder splashing and loss problems during the laser cladding process are relatively controllable. The repair consistency and surface roundness are easier to ensure, and the batch industrial repair of scrapped non-magnetic drill rods can be stably realized. A single coaxial powder-feeding laser cladding equipment can complete the repair of 8 to 12 non-magnetic drill rods with a diameter of 73 to 105 mm per day; the repair cost of a single drill rod is only about 35% of the purchase price of a brand new non-magnetic drill rod, and the repaired drill rod can be repaired and reused twice, reducing the overall procurement and maintenance costs by more than 60%. This Stellite 6 powder utilization rate is ≥92%, compared to the 65% material utilization rate of arc welding, significantly reducing the waste of precious cobalt, chromium, and tungsten alloys. The low-heat-input processing generates minimal smoke and dust, meeting the green repair manufacturing standards for drilling equipment. After repair, the drill pipe's factory inspection checklist includes six indicators: outer diameter tolerance, surface roughness, Rockwell hardness, relative magnetic permeability, penetrant testing, and electrochemical corrosion sampling inspection. Only drill pipes meeting all these standards can be delivered for downhole use.

[0045] Comparative Example 1 (Ni-based powder cladding using the same process) Conventional non-magnetic nickel-based alloy powder was used to replace Stellite 6, and the remaining pretreatment, laser cladding, and post-treatment procedures were completely consistent with those in Example 1. Test results: The repair layer hardness was 34~37 HRC, and the corrosion current density in 3% NaCl solution was only 4% lower than that of the substrate. Its corrosion resistance was basically the same as the substrate, which could not meet the requirements for long-term service in highly corrosive wells.

[0046] Comparative Example 2 (316L stainless steel powder multilayer cladding) 316L stainless steel powder with a thickness of 45~106μm was used for multi-layer repair, matching the complete set of cladding parameters from Example 1. Test results showed that inclusion defects existed between the multi-layer cladding layers, the corrosion current density was higher than that of the 1Cr18Mn18N substrate, and the corrosion resistance was inferior to that of the substrate.

[0047] Comparative Example 3 (Repair via conventional metal arc welding) The joint of a non-magnetic drill rod of the same specification (Φ89mm) was repaired using industry-standard metal powder-cored wire. Test results: Relative magnetic permeability of the weld overlay. m r =1.018>1.01, losing the conditions for non-magnetic use; the width of the heat-affected zone is 3.1mm, and the bonding strength is only 410MPa. It is prone to peeling and delamination during short-term downhole service.

[0048] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A laser cladding repair method for a non-magnetic drill rod, wherein the base material of the non-magnetic drill rod is 1Cr18Mn18N non-magnetic stainless steel, characterized in that, Includes the following steps: Step 1: Pre-treatment of the repair area: The area to be repaired on the non-magnetic drill rod substrate is machined to remove the surface damage layer, cleaned and then sandblasted to make the surface roughness Ra of the repaired surface reach 10-25 μm. Then, preheating treatment is performed at a temperature of 350-450 ℃. Step 2, Preparation of Repair Welding Material: Dry the Stellite 6 cobalt-based alloy powder; Step 3: Laser Cladding Repair Layer: The area to be repaired is laser-clad with dried Stellite 6 cobalt-based alloy powder to form a repair layer. The laser cladding process parameters are: laser power 1.8–2.2 kW, spot diameter 2.5–3.5 mm, scanning speed 8–15 mm / min, powder feed rate 200–300 mm³ / min, scanning interval 1.2–1.8 mm, protective gas is argon, gas flow rate 12–18 L / min; the cladding path adopts a spiral trajectory along the axis of the non-magnetic drill rod, covering the outer circumferential surface of the area to be repaired. The thickness of a single cladding layer is 1.2–1.8 mm, with a total of 2–3 layers claddingd, for a total thickness of 3–5 mm. Step 4: Post-cladding treatment: After cladding, cool to room temperature and polish the surface of the cladding layer to make the surface roughness Ra ≤ 1.6 μm.

2. The laser cladding repair method for a non-magnetic drill rod according to claim 1, characterized in that, The sandblasting process described in step one uses brown corundum sand with a particle size of 30-40 mesh.

3. The laser cladding repair method for a non-magnetic drill rod according to claim 1, characterized in that, The cleaning described in step one involves using anhydrous ethanol to remove oil stains from the surface to be repaired.

4. The laser cladding repair method for a non-magnetic drill rod according to claim 1, characterized in that, The drying temperature in step two is 100–150 °C, and the drying time is 1.5–3 h.

5. The laser cladding repair method for a non-magnetic drill rod according to claim 1, characterized in that, The laser cladding process parameters described in step three are as follows: laser power 1.9 kW, spot diameter 3 mm, scanning speed 10 mm / min, powder feeding rate 250 mm³ / min, scanning spacing 1.5 mm, and argon gas flow rate 15 L / min.

6. The laser cladding repair method for a non-magnetic drill rod according to claim 1, characterized in that, The cooling described in step four is natural cooling.

7. The laser cladding repair method for a non-magnetic drill rod according to claim 1, characterized in that, After the sandblasting treatment described in step one, the surface dust is blown away, and then the preheating treatment is performed.

8. The laser cladding repair method for a non-magnetic drill rod according to claim 1, characterized in that, The corrosion current density of the repair layer in 3% NaCl solution at room temperature is lower than that of the 1Cr18Mn18N non-magnetic stainless steel substrate, and the relative magnetic permeability of the repair layer is lower. μ r Less than 1.

01.

9. The laser cladding repair method for a non-magnetic drill rod according to claim 8, characterized in that, The Rockwell hardness of the repair layer is 39-42 HRC, and the Rockwell hardness of the 1Cr18Mn18N non-magnetic stainless steel substrate is 35-40 HRC.

10. A surface-repairing non-magnetic drill rod, prepared by the laser cladding repair method for the non-magnetic drill rod according to any one of claims 1 to 9, characterized in that, The system includes a non-magnetic drill rod substrate, on which a laser cladding repair layer is formed from Stellite 6 cobalt-based alloy powder via laser cladding. The laser cladding repair layer has a thickness of 3–5 mm, consists of 2–3 layers, has a surface roughness Ra ≤ 1.6 μm, and a Rockwell hardness of 39–42 HRC. The laser cladding repair layer exhibits superior corrosion resistance compared to the non-magnetic drill rod substrate, and its relative magnetic permeability is [not specified]. μ r Less than 1.01.